2022
DOI: 10.1021/acscatal.1c05386
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Nitrenoid Reductive Elimination Pathway in Nickel-Catalyzed C–N Cross-Coupling

Abstract: Whereas the (bisphosphine)Ni-catalyzed C−N cross-coupling of (hetero)aryl (pseudo)halides with NH nucleophiles represents a useful method for the synthesis of (hetero)anilines, our mechanistic understanding of such cross-couplings is incomplete, especially regarding key C−N reductive elimination steps that are often invoked as turnoverlimiting. In this combined experimental and computational study, we provide evidence of a bifurcated C−N reductive elimination pathway for cross-couplings of tBuNH 2 and (aryl′)S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…To overcome this challenge, we hypothesized that a strong Lewis base might competitively bind the BBN Lewis acid, thus rendering the Ad-NH unit available for C−N reductive elimination. When 6a was treated with a combination of 9-azajulolidine and sodium t-pentoxide, 101 we observed the reductive elimination product N-phenyl-N-adamantyl amine in 26% yield (Figure 11). 102,103 These results represent a proof of principle that reductive elimination can be induced using a suitable set of reagents.…”
Section: Studies Toward the Generation And Reactivity Of A Ni(ii) Imi...mentioning
confidence: 76%
“…To overcome this challenge, we hypothesized that a strong Lewis base might competitively bind the BBN Lewis acid, thus rendering the Ad-NH unit available for C−N reductive elimination. When 6a was treated with a combination of 9-azajulolidine and sodium t-pentoxide, 101 we observed the reductive elimination product N-phenyl-N-adamantyl amine in 26% yield (Figure 11). 102,103 These results represent a proof of principle that reductive elimination can be induced using a suitable set of reagents.…”
Section: Studies Toward the Generation And Reactivity Of A Ni(ii) Imi...mentioning
confidence: 76%
“…Access to 7 gave us a unique opportunity to stoichiometrically observe and study N−H deprotonation and subsequent C−N reductive elimination from an on-cycle amine-bound Ni complex. 83,84 We found that combining 7 with a slight excess of NaOt-Bu in a stoichiometric NMR study under inert atmosphere gave C−N coupled product in 89% NMR yield (Figure 8A), which had reached maximum conversion by the time the spectrum was taken (<5 min). This indicates that the deprotonation and reductive elimination steps occurred rapidly, even at room temperature, suggesting that the C−N bond-forming transition state barrier from the deprotonated complex is low.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Access to 6 gave us a unique opportunity to stoichiometrically observe and study N-H deprotonation and subsequent C-N reductive elimination from a catalytically oncycle amine-bound Ni complex. 76,77 We found that combining 6 with a slight excess of NaOt-Bu in a stoichiometric NMR study under inert atmosphere gave C-N coupled product in 89% NMR yield (Scheme 4A), which had reached maximum conversion by the time the spectrum was taken (< 5 minutes). This indicates that the deprotonation and reductive elimination steps occurred rapidly, even at room temperature, suggesting that C-N bond-forming transition state barrier from the deprotonated complex is low.…”
Section: Scheme 4 Stoichiometric C-n Reductive Elimination Andmentioning
confidence: 99%